2015
DOI: 10.1002/2014ja020865
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly pitch angle distribution of relativistic electrons in the outer radiation belt: Evidence of nonadiabatic scattering

Abstract: In this paper we investigate the scattering of relativistic electrons in the nightside outer radiation belt (around the geostationary orbit). We consider the particular case of low geomagnetic activity (|D st | < 20 nT), quiet conditions in the solar wind, and absence of whistler wave emissions. For such conditions we find several events of Van Allen probe observations of butterfly pitch angle distributions of relativistic electrons (energies about 1-3 MeV). Many previous publications have described such pitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 109 publications
(233 reference statements)
0
36
0
Order By: Relevance
“…While so far we do not have a good explanation for such a small dependence on P dyn , this feature reasonably agrees with the results of Selesnick and Blake [, their Figures 7–9], which demonstrated that with increasing geomagnetic activity the relativistic electron anisotropies do not change as much as is predicted, particularly on the nightside where the butterfly distributions often occur. Another possible explanation of relativistic electron butterfly PADs suggests that they can be shaped due to relativistic electron scattering in the equatorial plane of magnetic field lines that are locally deformed by currents of hot ions injected into the inner magnetosphere [ Artemyev et al ., ].…”
Section: Discussionmentioning
confidence: 60%
“…While so far we do not have a good explanation for such a small dependence on P dyn , this feature reasonably agrees with the results of Selesnick and Blake [, their Figures 7–9], which demonstrated that with increasing geomagnetic activity the relativistic electron anisotropies do not change as much as is predicted, particularly on the nightside where the butterfly distributions often occur. Another possible explanation of relativistic electron butterfly PADs suggests that they can be shaped due to relativistic electron scattering in the equatorial plane of magnetic field lines that are locally deformed by currents of hot ions injected into the inner magnetosphere [ Artemyev et al ., ].…”
Section: Discussionmentioning
confidence: 60%
“…During magnetic activities, the observation of butterfly PAD can be located within L = 6 at all magnetic local time (MLT) [Lyons and Williams, 1975;Sibeck et al, 1987]. Currently, seven mechanisms have been proposed to explain the formation of the butterfly PAD during magnetic activities: (a) wave-particle interaction with magnetosonic waves and chorus waves [Horne et al, 2005a;Xiao et al, 2015;Li et al, 2016bLi et al, , 2016aChen et al, 2015;Maldonado et al, 2016], (b) nonlinear resonance with oblique electromagnetic ion cyclotron waves [Wang et al, 2016], (c) wave-particle interaction with hiss waves, lightening-generated whistlers and ground VLF transmitters [Albert et al, 2016], (d) outward adiabatic transports [Su et al, 2010], (e) magnetopause shadowing effect [e.g., Wilken et al, 1986], (f ) substorm injection combined with drift shell splitting [Sibeck et al, 1987], and (g) nonadiabatic scattering due to the field line curvature scattering [Artemyev et al, 2015] and adiabatic effect caused by ring current through the conservation of electron's magnetic moment [Lyons, 1977].…”
Section: 1002/2017gl072558mentioning
confidence: 99%
“…The mechanisms controlling ultrarelativistic electron acceleration and loss have long been a fundamental topic of radiation belt studies [ Reeves et al ., , ; Thorne et al ., ; Turner et al ., ]. More recently, because of the unprecedented high angular resolution of particle measurements made by the Van Allen Probes, the pitch angle distributions have become the focus of quantifying various kinds of wave‐particle interactions [ Ni et al ., ; Artemyev et al ., ; Vasko et al ., ]. Three basic kinds of pitch angle distributions are typically identified: 90°‐peaked, flat‐top (or pancake), and butterfly distributions [ West et al ., ; Baker et al ., ; Fritz et al ., ; Horne et al ., ; Meredith et al ., ; Gannon et al ., ; Zhao et al ., ; Fennell et al ., ].…”
Section: Introductionmentioning
confidence: 99%